Fundamentación doctrinaria para ilustrar jurídicamente la adopción y garantizar los derechos a las peersonas del mismo sexo.Quevedo. - Cedeño Mieles, Daysi Marianela (2015)
This Thesis, whose theme is "legally illustrate doctrinal Rationale for adoption and guarantee the rights to same-sex" is composed of six chapters, in which aspects and concepts of the subject under investigation are detailed. In chapter I, comprises the introduction, a summary of the adoption to same-sex becomes; on the critical, the reality on the impediments that have the same sex to adopt targets; objectives, general and specific notes; the hypothesis, the independent and dependent variables and resources are detailed. In chapter II, the theoretical framework, consisting of background research, rationale: Doctrine, Jurisprudence, Law and Comparative Law under study, which referred to different laws, especially the Constitution of the Republic of Ecuador is based. In chapter III and IV consists methodology, the methods used are determined, the techniques applied in the field, applying surveys citizens of Canton Buena Fe, Lawyers in free practice and interviews with such results tabulation, analysis and data processing was performed, the research report was prepared and proceeded to hypothesis testing. In chapter V and VI, the conclusions and recommendations are made; and the proposal to formulate a doctrinal study of the different legislations which have adopted a same sex.